Grafting of functional methacrylate polymer brushes by photoinduced SET-LRP. Issue 45 (26th October 2016) - Vorobii, Mariia; Pop-Georgievski, Ognen; de los Santos Pereira, Andres; Kostina, Nina Yu.; Jezorek, Ryan; Sedláková, Zdeňka; Percec, Virgil; Rodriguez-Emmenegger, Cesar
Abstract : The growth of polymer brushes from a variety of methacrylate monomers was accomplished using UV light as a polymerization trigger. Abstract : Photoinduced surface-initiated single electron transfer living radical polymerization (SET-LRP) is a versatile technique for the preparation of polymer brushes. The vast diversity of compatible functional groups, together with a high end-group fidelity that enables precise control of the architecture, makes this approach an effective tool for tuning the properties of surfaces. We report the application of photoinduced SET-LRP for the surface-initiated grafting of polymer brushes from a wide range of methacrylate monomers for the first time. The living character of the process was demonstrated by the linear evolution of the polymer brush thickness in time, the ability to reinitiate the polymerization for the preparation of well-defined block copolymers, and also by X-ray photoelectron spectroscopy depth profiling. The surface patterning with these brushes could be achieved simply by restricting the irradiated area. The ability of poly(methacrylate) brushes prepared in this way to prevent non-specific protein adsorption is also demonstrated, indicating the suitability of this procedure for advanced applications.